2020
DOI: 10.18553/jmcp.2020.26.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Annual Health Care Costs for Adults with Type 1 Diabetes in the United States

Abstract: BACKGROUND: Diabetes health care resource utilization (HCRU) studies tend to focus on patients with type 2 diabetes (T2D) or pool patients with T2D and type 1 diabetes (T1D). There is a paucity of recent data on the cost of treating patients with T1D in the United States.OBJECTIVES: To (a) estimate the per-patient per-year (PPPY) HCRU and costs, from a payer perspective, associated with treating U.S. adults with T1D and (b) compare these with the HCRU and costs for patients with T2D.METHODS: This retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Because the onset of T1DM typically arises early, effective disease management is imperative to limit its health and economic impact [14]. Existing literature has highlighted the higher cost of treating T1DM compared with T2DM [15]. To understand the economic impact of T1DM, the IQVIA CDM is used to evaluate the health care resource utilization over a 12-month period in patients with controlled and uncontrolled T1DM in the public health care sector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the onset of T1DM typically arises early, effective disease management is imperative to limit its health and economic impact [14]. Existing literature has highlighted the higher cost of treating T1DM compared with T2DM [15]. To understand the economic impact of T1DM, the IQVIA CDM is used to evaluate the health care resource utilization over a 12-month period in patients with controlled and uncontrolled T1DM in the public health care sector.…”
Section: Discussionmentioning
confidence: 99%
“…In the base-case analyses, second-order uncertainty is not applied, and stability of outcomes is reached through a run of 1000 patients through 1000 iterations. There is an existing and emerging body of evidence looking to quantify health care resource utilization and appropriately describe economic considerations in the management of people living with T1DM [14,15]. There is, however, a lack of such data within developing nations that are required to facilitate policy discussions pertaining to the health and economic impact of T1DM in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Heald et al reported that type 1 diabetes results in an average of 7.6 years of life lost [2], whilst Livingstone et al reported that it is associated with approximately 11 years of life lost for men and 13 years for women [3]. Type 1 diabetes also has significant societal costs, including loss of work days [1] and health care related costs [4].…”
Section: Introductionmentioning
confidence: 99%
“…The current COVID-19 pandemic has additionally highlighted that diabetes is a major risk factor for severe bouts of disease (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In particular, type 1 diabetes (T1D) is a significant burden that typically appears during adolescence and requires life-long insulin administration and blood glucose monitoring (19). T1D is a chronic disease characterized by the autoimmune destruction of pancreatic islet b cells (20).…”
Section: Introductionmentioning
confidence: 99%